Joe Celko's thinking in sets : auxiliary, temporal, and virtual tables in SQL - Celko, Joe (Morgan Kaufmann series in data management systems., 2008)
Perfectly intelligent programmers often struggle when forced to work with SQL. Why? Joe Celko believes the problem lies with their procedural programming mindset, which keeps them from taking full advantage of the power of declarative languages. The result is overly complex and inefficient code, not to mention lost productivity. This book will change the way you think about the problems you solve with SQL programs. Focusing on three key table-based techniques, Celko reveals their power through detailed examples and clear explanations. As you master these techniques, youll find you are able to conceptualize problems as rooted in sets and solvable through declarative programming. Before long, youll be coding more quickly, writing more efficient code, and applying the full power of SQL Filled with the insights of one of the worlds leading SQL authorities - noted for his knowledge and his ability to teach what he knows. Focuses on auxiliary tables (for computing functions and other values by joins), temporal tables (for temporal queries, historical data, and audit information), and virtual tables (for improved performance). Presents clear guidance for selecting and correctly applying the right table technique.